2020
DOI: 10.1038/s41598-020-75706-1
|View full text |Cite
|
Sign up to set email alerts
|

MDMA-assisted psychotherapy for treatment of anxiety and other psychological distress related to life-threatening illnesses: a randomized pilot study

Abstract: The success of modern medicine creates a growing population of those suffering from life-threatening illnesses (LTI) who often experience anxiety, depression, and existential distress. We present a novel approach; investigating MDMA-assisted psychotherapy for the treatment of anxiety in people with an LTI. Participants with anxiety from an LTI were randomized in a double-blind study to receive MDMA (125 mg, n = 13) or placebo (n = 5) in combination with two 8-h psychotherapy sessions. The primary outcome was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(144 citation statements)
references
References 52 publications
4
139
0
1
Order By: Relevance
“…While we did not directly measure depressive symptoms and anxiety, our findings regarding empathogens use contradict the common notion of MDMA induced mood disorders. What is more, MDMA assisted psychotherapy was recently found to decrease anxiety and distress in patients with life-threatening diseases (Wolfson et al, 2020), and social anxiety in patients with autism (Danforth et al, 2018). While these findings are preliminary, together with our result they point out that psychological problems commonly associated with MDMA use should be carefully revisited.…”
Section: Relation Of Emotional Reactivity and Self-consciousness With Other Substances And With Meditation Practicesupporting
confidence: 57%
“…While we did not directly measure depressive symptoms and anxiety, our findings regarding empathogens use contradict the common notion of MDMA induced mood disorders. What is more, MDMA assisted psychotherapy was recently found to decrease anxiety and distress in patients with life-threatening diseases (Wolfson et al, 2020), and social anxiety in patients with autism (Danforth et al, 2018). While these findings are preliminary, together with our result they point out that psychological problems commonly associated with MDMA use should be carefully revisited.…”
Section: Relation Of Emotional Reactivity and Self-consciousness With Other Substances And With Meditation Practicesupporting
confidence: 57%
“…In most studies, psychedelic administration led to a reduction in depressive symptoms [ 33 , 34 , 35 , 36 , 42 , 43 , 44 ]. Among the randomized controlled trials, all four studies with psilocybin, three with MDMA, and one with DMT demonstrated significant efficacy in reducing the symptoms of depression and in reducing amygdala hyperactivity, a distinctive feature of depression.…”
Section: Discussionmentioning
confidence: 99%
“…The changes were similar in both groups but more strongly expressed in the MDMA group. The MDMA treatment was well tolerated, and no serious adverse events were reported [ 35 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While two SSRIs have been approved for PTSD, pooled data indicate that MDMA-assisted psychotherapy may constitute "a substantial improvement over available pharmacotherapies in terms of safety and efficacy" (54). Other research suggests MDMA-assisted psychotherapy may be efficacious for treating social anxiety among adults with autism, end-of-life anxiety/psychological distress, alcohol use disorder and eating disorders (55)(56)(57)(58). Based on these findings, researchers recommend that MDMA-assisted psychotherapy be expeditiously evaluated for clinical use (50).…”
Section: Mdma-assisted Psychotherapy For Trauma-related Disordersmentioning
confidence: 99%